Unboxing corporate liability: Section 17A MACC Act 2009 - Sharija Che Shaari (Universiti Malaysia Sabah, 2020)
Malaysia strives to be one of the world's top 10 'cleanest' nation by 2030. Though it is still quite a long way, the Government of Malaysia has shown that it “walks the talk” by amending the Malaysian Anti-Corruption Commission Act 2009 (MACC Act 2009) in 2018 (which came into effect on 1 June 2020), inter alia, to introduce statutory corporate liability provision for bribery and corruption under section 17A. This paper aims to explore the roots of section 17A and how it can be implemented. The study deploys the doctrinal method which is based on the secondary data by analysing the primary legal sources (statutes) and secondary sources (decided cases). This paper presents the salient features of section 17A such as commercial organisation, associated person, adequate measures and penalty. Before section 17A came into effect, the MACC Act 2009 only focuses on the prosecution of individuals involved in corruption. Section 17A was enacted to enable commercial organisation involved in corruption activities to be subjected to legal action and persons associated with the commercial organisation will be deemed to commit a corrupt act to obtain or retain business or an advantage in the conduct of business for the commercial organisation unless it can be proven that adequate measures have been put in place. Business owners and senior officers in a commercial organisation must understand the far-reaching implications of section 17A though it is postulated that small commercial organisation may not be aware and/or understand its implication. In conclusion, the efforts and initiatives of the Government of Malaysia to tackle corruption are commendable.